The Effect of Self-Efficacy, Human Resource Quality, Resilience on Burnout and Employee Performance at PT. Penaraya Valencia Jakarta Timur - Maria Alni Lau Go’o; Tri Andjarwati; Mochammad Sihab Ridwan (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2025)
Infrastructure development in Indonesia has progressed significantly, with the government prioritizing public facility improvements in quality and quantity. PT. Penaraya Valencia, a national private consulting firm, supports government and private projects by providing building planning and management consulting services. The company handles diverse projects under varying conditions, requiring efforts to enhance employee performance. However, heavy workloads and challenging situations can lead to stress and burnout, impacting employee performance. This study aims to analyze the effects of self-efficacy, human resource quality, and resilience on burnout and employee performance at PT. Penaraya Valencia in East Jakarta. A sample of 96 employees was analyzed using Structural Equation Modeling (SEM) with SmartPLS software, complemented by SPSS for descriptive analysis. The findings reveal: (1) self-efficacy negatively and significantly affects burnout, (2) self-efficacy positively and significantly impacts employee performance, (3) human resource quality does not significantly affect burnout, (4) human resource quality positively and significantly impacts employee performance, (5) resilience negatively and significantly affects burnout, (6) resilience positively and significantly impacts employee performance, (7) burnout negatively and significantly affects employee performance, (8) self-efficacy significantly influences performance through burnout mediation, (9) human resource quality does not significantly affect performance through burnout mediation, and (10) resilience significantly impacts performance through burnout mediation. These findings emphasize the importance of enhancing self-efficacy, resilience, and human resource quality to minimize burnout and improve employee performance.